Case report: Co-occurring autism spectrum disorder (Level One) and obsessive-compulsive disorder in a gender-diverse adolescent - Guastello, Andrea D.; Lieneman, Corey; Bailey, Brittany; Munson, Melissa; Barthle-Herrera, Megan; Higham, Miranda; Druskin, Lindsay; McNeil, Cheryl B. (Frontiers in Psychiatry, 2023)
This fictionalized case report captures the common themes and considerations during the diagnostic assessment and behavioral treatment of adolescents demonstrating symptoms of autism spectrum disorder (ASD), obsessive-compulsive disorder (OCD), and attention-deficit/hyperactivity disorder (ADHD), as well as gender-diversity concerns. Our patient was a white, non-Hispanic 17-year-old individual who identified as gender-neutral but had been assigned female at birth. Symptoms presented were social withdrawal, rigid rule-following behavior, unusual repetitive behavior, impairments in social communication skills, sensory sensitivity, body dissatisfaction, self-injury, and anxiety related to contamination, perfectionism, and social interactions. These symptoms contributed to functional impairment with school attendance, school achievement, family relationships, and the activities of daily living. This case report summarizes instruments employed for differential diagnosis concerning cognitive functioning, ASD, OCD, ADHD, depression, anxiety, and commonly co-occurring repetitive behavior. This patient was ultimately diagnosed with ASD, level one for both social communication and restricted, repetitive behaviors, without accompanying intellectual or language impairment; OCD with panic attacks; gender dysphoria; major depressive disorder (single episode and moderate); and ADHD. The subsequent 40-session course of cognitive-behavioral therapy with exposure and response prevention (CBT/ERP) to treat OCD tailored to an individual with ASD and gender diversity concerns is described in detail. Components of family involvement are highlighted. As a result, significant improvements in school attendance, OCD symptoms, depression, social relationships, and adaptive functioning were measured. Lastly, recommendations for clinicians are summarized.